Strategi Kebijakan Pengembangan Sagu Berbasis Sentra Industri Kecil Menengah (IKM) - Syamsuadi, Amir; Hartati, Seri; Trisnawati, Liza; Arisandi, Diki (Jurnal Inovasi Ilmu Sosial dan Politik (JISoP), 2020)
Based on estate statistics collected by the Ministry of Agriculture of the Republic of Indonesia, that in 2017 the total area of plantations producing Sago Islands Regency reaches 91,944 hectares and plant production of 418,802 tons. The number increased from 2 years earlier, namely in 2015 sago plant area was 83,691 ha with a production yield of 366,032 tons and in 2016 sago plant area was 89,611 ha with a production yield of 377,914. This study tries to trace the direction of the sago-based policy development Center for Small and Medium Industries in the Meranti Islands District. This research was conducted with a qualitative approach which is research that focuses on the concepts that arise from the data. The results of the analysis and interpretation of data in the form of exposure to the situation under study and then given a narrative and systematic explanation. The results showed that policies in order to encourage the development of sago-based Small and Medium Industrial Centers in the Regency of Meranti Islands including carried out with scenarios of structuring the location of activities, land use plans, efforts to map the transportation network system plans, telecommunications, electricity and clean water.